Effect of varying levels of nitrogen on growth, yield, quality and profitability of transplanted fennel (Foeniculum vulgare Mill.) - Kumar, R L Bhardwaj, D (Journal of Spices and Aromatic Crops, 2016)
Field experiments were conducted at two adjoining farmer’s field in tribal area of district Sirohi (Rajasthan) during two successive seasons from July 2012 to March 2013 and July 2013 to March 2014 to study the impact of varied levels of nitrogen (60, 90, 120 & 150 kg N ha-1) on production, quality and profitability of transplanted fennel (Foeniculum vulgare). Application of nitrogen @120 kg ha-1 recorded the highest stem girth, number of roots plant-1, root length, fresh weight of root and root: shoot ratio. The maximum value of number of umbels plant-1, umbellate umbel-1, number of seeds umbel-1, test weight, seed yield, straw yield, harvesting index was also reported in same treatment. Similarly, volatile and total oil content, soluble sugar, total carbohydrate and overall quality of seeds were also higher with application of 120 kg N ha-1, whereas, disease incidence significantly increased with application of higher dose of nitrogen (150 kg N ha-1). The maximum net return and highest benefit: cost ratio was also recorded with application of 120 kg N ha-1. However, some of the growth parameters (plant height, number of primary and secondary branches plant-1, number of leaves, fresh weight of shoot and duration of flowering, protein and nitrogen content in seed were more with 150 kg N ha-1.